Frequency analysis of electrostatic cantilever-based MEMS sensor - Shoaib, M. (Institute of Electrical and Electronics Engineers Inc., 2015)
This paper presents an analytical approach to model the dynamic behavior and predict the frequency of electrostatic cantilever based MEMS (Microelectromechanical system) sensor for mass detection. The concept of dynamic mass is used to formulate the resonance frequency in damped and undamped medium. In the modeling, electrostatic force is coupled with the bending moment of cantilever to produce actuation at a resonance frequency. Mass of blood cells is used as an external load on the cantilever which results in shift in resonance frequency. This shift due to additional mass is sensed by the piezoresistive mechanism. The device analytical model is integrated using Simulink tool to study the dynamic behavior. The same device is then designed using COMSOL tool and FEM analysis is performed. The analytical results are compared with the simulated results. Â© 2015 IEEE.